Estado, poder e fetichismo: comunicação e mensuração do poder - Diniz, Carlos Augusto de Oliveira (2017)
In the present work an approach is made on the power and for that reason an analysis of some of its several faces was made, among them its fixation in the relations between parties, the role of the State as institution capable of promoting a convergence of the power for itself, Power has also been analyzed as analogous to the idea of value in a society based on relations of exchange. The general objective is to confirm or not the possibility of measuring power. The specific goal is to define the size of the power on any of its faces. In the present approach the method used will be the deductive, since it starts from a generic sphere to a specific one, that is, from the interpretation of a general rule so that the specific cases can be understood. As for the justification of the present work, it is due to the academic trajectory of the author that allowed him to perceive that there is no hierarchy between powers, that is, he is stable, constant, and that there are no "holders" of power either, Author to better understand this fact. In this line some hypotheses have arisen that power may have a size, but it is smaller than one might imagine, that is, power has a size that limits the survival of relations, and then What is done is precisely to inflate this perception about what the real size of power would be in order to make it believe that it really is large, that there are some with great power and others with little power, another hypothesis is that the measurement of power Must be made from the establishment of the material limits of power, that is, established such limits the power can be measured. From the methodological point of view, it was based on proven historical facts for the construction of a reasoning that allows to analyze the power in all their faces in the most varied relations, for that reason a way based on the deduction, but we tried to walk with freedom, Especially from the vantage point of a linearity of thought, that is, with a certain amount of discontinuity of the facts. The result was that communication that is central to the social relational process is an important element capable of altering perception about the size / measure of power and this contributes to two facts, first to deny the fragility of power and second to maintain society Far from sedition